Sports, exercise, and nutritional genomics : current status and future directions - Barh, Debmalya; Ahmetov, Ildus I. (Academic Press, an imprint of Elsevier, 2019)
Sports, Exercise, and Nutritional Genomics: Current Status and Future Directions is the first reference volume to offer a holistic examination of omics-driven advances across different aspects of exercise and sports physiology, biochemistry, sports medicine, psychology, anthropology, and sports nutrition; and highlighting the opportunities towards advance personalized training and athlete health management. More than 70 international experts from 14 countries have discussed key exercise and sport-related themes through the prism of genomics, epigenomics, transcriptomics, proteomics, metabolomics, telomere biology, talent in sport, individual differences in response to regular physical activity, that in the future may empower coaches, sports physicians, fitness experts, genetic counselors, and translational scientists to employ various omics data and approaches in improving health and physical performance of people participating in sports and exercise activities. Contributors address current knowledge of genetic influence on athletic performance, individual responses to exercise training, as well as the genetics of musculoskeletal phenotypes, exercise-related injuries, flexibility, and neurodegenerative disorders in athletes. Finally, performance-related and psychological traits associated with epigenetic, transcriptomic and metagenomic biomarkers are also considered, along with nutritional and pharmacogenomic aids in sports medicine and personalized nutrition.